Impact of regular physical activity and sports on school performance among girls and boys aged between 6 and 10 years (Impacto de la actividad física regular y los deportes en el rendimiento escolar entre niñas y niños de entre 6 y 10 años) - Bekhechi, Amina Kheira; Khiat, Belkacem (Retos, 2019)
Abstract. This longitudinal study seeks to show if sport has an impact on the school results and also on cognitive functioning, and if this causal link is significantly important. An experimental group of 55 students that practice out-of-school sports, at a rate of 3 times a week and a reference group of 55 students that don’t practice out of school sports, their age is between 6 and 10 years old, both male and female from an elementary schools of the town of Oran (Algeria), they were followed during 15 month (five quarters). The socio-demographic data were collected by a questionnaire intended for the students of the two groups, and the administrative school results at the end of each quarter. An intelligence test of the CPM (Raven’s Coloured Progressive Matrices) was administered at the end of the fifth trimester to assess the main cognitive abilities in both groups. Students that practice out-of-school sports have general school averages and a significantly higher level of intelligence than students that don’t (p < 0.05) where sport girls have overall academic averages significantly higher than sport boys (p = 0.025). As noted by many similar studies, the practice of a physical-activity and sport regular seem to have a very positive impact on the academic performance and also on cognitive functioning. Resumen. Este estudio longitudinal busca mostrar si el deporte tiene un impacto en los resultados escolares y también en el funcionamiento cognitivo, y si este vínculo causal es significativamente importante. Un grupo experimental de 55 estudiantes que practican deportes fuera de la escuela, a una tasa de 3 veces por semana y un grupo de referencia de 55 estudiantes que no practican deportes fuera de la escuela, su edad es entre 6 y 10 años, Tanto hombres como mujeres de una escuela primaria de la ciudad de Orán (Argelia), fueron seguidos durante 15 meses (cinco cuartos). Los datos socio demográfico se recopilaron mediante un cuestionario destinado a los estudiantes de los dos grupos y los resultados de la escuela administrativa al final de cada trimestre. Se administró una prueba de inteligencia de CPM (Matrices progresivas de color de Raven) al final del quinto trimestre para evaluar las principales habilidades cognitivas en ambos grupos. Los estudiantes que practican deportes fuera de la escuela tienen promedios escolares generales y un nivel de inteligencia significativamente más alto que los estudiantes que no lo hacen (p < 0.05) donde las chicas deportistas tienen promedios académicos generales significativamente más altos que los varones deportivos (p = 0.025). Como lo observaron muchos estudios similares, la práctica de una actividad física y un deporte regular parecen tener un impacto muy positivo en el rendimiento académico y también en el funcionamiento cognitivo.